Ideological aspects of illustrative zones in modern Arab dictionaryon examples of "Big dictionary" CAIRO ACADEMY Arabic - Shayakhmetov О М; Kydyrbayev К А (Journal of Oriental Studies, 2016)
In an article on actual examples onthe first time considered the ideological component in modern Arabic dictionary at the example of the "Big Dictionary" of Arabic Language Academyin Cairo, addressed the problem of the selection and arrangement of illustrative material, discusses the degree of functionality and the proportion of empiricism of religious texts in describing thelexical unit.